A review of influence of environment and process parameters on glucosinolate-myrosinase system from Brassica - Valéria Dal Práa, Natália Silva Jardima, Carolina Bolssoni Dolwitscha, Marcio Antônio Mazuttib, Carine Vianaa, Denise Bohrera, Paulo Cicero Nascimentoa, Leandro Machado de Carvalhoa, Marcelo Barreto da Silvac, Camilo Amaro de Carvalhod, Marcelo Barcellos da Rosaa (Journal of Applied Pharmaceutical Science, 2013)
The family Brassicaceae has been very studied due to the pharmacologic properties of the glucosinolates (GLS) and their hydrolysis products, which are associated with the action of an endogenous thioglucosidase myrosinase. Factors such as climate, soil, genotype, seasonal variation, processing, extraction quantification can affect the enzyme activity and stability, leading to increase or decrease the hydrolysis of GLS. Based on this aspect, the main objective of this work is present a review concerning the glucosinolate-myrosinase system, influence of climate and genotype to seasonal variation in the glucosinolate-myrosinase system, effect of thermal and high hydrostatic pressure treatments on the GLS content, as well as, the isolation and quantification of GLS from Brassica.
Keywords: Brassica, environmental parameter